Tailoring of physical properties of RF-sputtered ZnTe films: role of substrate temperature - Devi, Kafi; Rani, Usha; Kumar, Arun; Gupta, Divya; Aggarwal, Sanjeev (Beilstein Journal of Nanotechnology, 2025)
In this study, zinc telluride (ZnTe) films were grown on quartz substrates at room temperature, 300 °C, 400 °C, 500 °C, and 600 °C using RF sputtering. The thickness of the films has been found to decrease from 940 nm at room temperature to 200 nm at 600 °C with increasing substrate temperature. The structural investigation using grazing incidence angle X-ray diffraction revealed that films deposited at room temperature are amorphous; those deposited at other substrate temperatures are polycrystalline with a cubic zincblende structure and a preferred orientation along the [111] direction. An increase in crystallite size (from 37.60 ± 0.42 Å to 68.88 ± 1.04 Å) is observed with increased substrate temperature. This leads to a reduction in microstrain and dislocation density. The optical studies using UV–vis–NIR spectroscopy reveal that the transmittance of films increases with substrate temperature. Further, the shift in transmittance threshold towards lower wavelengths with substrate temperature indicates that the optical bandgap of the films can be tuned from 1.47 ± 0.02 eV to 3.11 ± 0.14 eV. The surface morphology of the films studied using atomic force microscopy reveals that there is uniform grain growth on the surface. Various morphological parameters such as roughness, particle size, particle density, skewness, and kurtosis were determined. Current–voltage characteristics indicate that the conductivity of the films increased with substrate temperature. The observed variations in structural, morphological, and optical parameters have been discussed and correlated. The wide bandgap (3.11 eV), high crystallinity, high transmittance, and high conductivity of the ZnTe film produced at 600 °C make it a suitable candidate for use as a buffer layer in solar cell applications.
Keywords: bandgap; physical properties; RF sputtering; substrate temperature; ZnTe